Promoting The Virtue of Obedience for The Minor Seminarians of Saint Joseph Minor Seminary, Sampran, Nakhon Pathom. - Kitcharoen, Akranon; Chumsriphun, Surachai; Phongsiri, Chartchai; Prasootsaengchan, Laddawan (Saengtham College Journal, 2023)
This mixed-method study aims to investigate : 1) how minor seminarians at Saint Joseph Minor Seminary in Sampran, Nakhon Pathom, practice obedience on their own; and 2) how guidelines for cultivating the virtue of obedience are developed for the minor seminarians at Saint Joseph Minor Seminary in Samphran, Nakhon Pathom. The sample of this study consisted of eighty-nine (89) seminarians of Saint Joseph Minor Seminary in Sampran, Nakhon Pathom. In this study, a set of questionnaires was used as the main research instrument. The obtained data were quantitatively analyzed using descriptive statistics, which includes the frequency, percentage, mean, and standard deviation. The data were collected through the focus group discussion with eleven experts, who were selected based entirely on researcher’s assessment known as selective sampling method. A focus group discussion was used, and the acquired data were analyzed using content analysis. The results of this research reveal : The minor seminarians at Saint Joseph Minor Seminary in Sampran, Nakhon Pathom, have a high level of self-practiced obedience (= 3.89, SD.= 0.419). When taken a careful consideration, the virtue of obedience was practiced at a high level both outside the seminary (= 3.91, SD.= 0.519) and inside the seminary (= 3.68, SD.= 0.417) The following recommendations are strongly advised for minor seminarians at Saint Joseph Minor Seminary to promote the virtue of obedience, according to research findings: 2.1 When giving the formation, all formators are expected to work collectively. For the future formation and growth of any potential priests, they should all have the same objective. The formators are strongly encouraged to make a concerted effort to help the seminarians realize the significance of this particular virtue to them. In order to facilitate the seminarians' formation and development processes and integrate psychological principles into their formation training, they should also create a strong and personal relationship with them. This also entails utilizing communication strategies and group-formation procedures that are appropriate for the current social conditions. Additionally, the formators have to put in every effort to arrange meetings with the seminarians' parents, teachers, and pastors. 2.2 The pastors should ensure that those who are interested in attending the priestly formation are well-prepared in their parish church and have a fundamental comprehension of the formation prior to their participation. The pastors should also have a good and intimate relationship with the seminarians or those who are interested in the priestly formation in their parish church. The pastors should also have a good and personal relationship with the seminarians or those who are interested in the priestly formation in their parish church. In addition, the pastors should seize every opportunity to interact with the formators of the seminary as frequently as necessary. 2.3 All teachers and educational formators should work collaboratively with Saint Joseph Minor Seminary to the best of their abilities in order to provide the seminarians with ongoing formation through the provision of role models and the development of respectful relationships with all seminarians. Teachers and educational formators should seize every opportunity to interact and communicate with seminary formators. 2.4 The parents of seminarians should collaborate with Saint Joseph Minor Seminary to the best of their abilities in order to facilitate the seminarians' ongoing formation. They must really work with the seminary, and there should be an opportunity for the parents and the formators to interact and communicate with one another. 2.5 The seminarians or those who are interested in participating in the priestly formation should have acquired a fundamental awareness of the seminary’s objectives and the patterns of priestly formation prior to enrolling at the seminary and/or starting the training process. This will assist them in comprehending and appreciating the conformity of the virtue of obedience. Seminarians should also have the courage to seek advice or counsel from their formators. This should be done on a regular basis.